2019
DOI: 10.3390/biom9120813
|View full text |Cite
|
Sign up to set email alerts
|

A Hepatic Scaffold from Decellularized Liver Tissue: Food for Thought

Abstract: Allogeneic liver transplantation is still deemed the gold standard solution for end-stage organ failure; however, donor organ shortages have led to extended waiting lists for organ transplants. In order to overcome the lack of donors, the development of new therapeutic options is mandatory. In the last several years, organ bioengineering has been extensively explored to provide transplantable tissues or whole organs with the final goal of creating a three-dimensional growth microenvironment mimicking the nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 143 publications
0
33
0
2
Order By: Relevance
“…Previous studies have shown that tissue-engineered livers are an attractive organ replacement solution for compensating the shortage of liver sources. Transplanting cells into a liver matrix made up of a decellularized scaffold that mimics the microstructure of native tissues is expected to provide a functional bionic liver [21][22][23][24][25][26][27]. Our study demonstrated that detergent perfusion through the portal vein created a translucent liver matrix while maintaining the native vasculature for adequate perfusion of constructs that were able to withstand physiological blood pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that tissue-engineered livers are an attractive organ replacement solution for compensating the shortage of liver sources. Transplanting cells into a liver matrix made up of a decellularized scaffold that mimics the microstructure of native tissues is expected to provide a functional bionic liver [21][22][23][24][25][26][27]. Our study demonstrated that detergent perfusion through the portal vein created a translucent liver matrix while maintaining the native vasculature for adequate perfusion of constructs that were able to withstand physiological blood pressures.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained demonstrated that it was possible to in vitro re-create a tissue-engineered trachea with mechanical properties that allow normal functioning, providing successful treatment for patients [ 166 ]. Following this, many studies using a single type of tissue-specific stem cells [ 158 , 170 , 181 , 182 , 183 , 184 , 185 ] or induced pluripotent cells [ 185 , 186 , 187 , 188 ] were carried out, and others are currently ongoing, in order to identify the best 3D supports able to boost cell differentiation and successfully produce in vitro functional tissues and organs for future possible transplantation. In parallel, both synthetic and biological scaffolds were repopulated with terminally differentiated cells, including fibroblasts [ 155 ], mature hepatocytes [ 189 , 190 , 191 ], and pancreatic endocrine [ 192 , 193 , 194 ], cardiac [ 195 ], and ovarian cells [ 196 ].…”
Section: Tissue and Organ Regeneration Approachesmentioning
confidence: 99%
“…Дефицит донорских органов для трансплантации печени при лечении терминальных стадий печеночной недостаточности диктует необходимость разработки альтернативных методов, к которым относятся технологии тканевой инженерии и регенеративной медицины [1,2].…”
Section: Introductionunclassified
“…Отметим, что взаимодействие клеток с полученным тканеспецифическим матриксом изучено не было. 1,3 , M.Yu. Shagidulin 1,3 , V.I.…”
Section: Introductionunclassified
See 1 more Smart Citation